Pregunta
upstudy study bank question image url

2 Change the subject of the formula to \( x \) 7.2.1 \( m=\sqrt{x^{2}}+a x \) 7.2.2 \( Q=m c(y-x) \) 7.2.3 \( m(m x-n)-n(n x-m)=m^{2} n^{2} \)

Ask by Phillips Schultz. in South Africa
Feb 18,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

To solve for \( x \) in each equation: 1. **7.2.1**: - If \( x \geq 0 \): \( x = \frac{m}{1 + a} \) - If \( x < 0 \): \( x = \frac{m}{a - 1} \) 2. **7.2.2**: \( x = y - \frac{Q}{m \cdot c} \) 3. **7.2.3**: \( x = \frac{m^2 n^2}{m^2 - n^2} \)

Solución

Below are the steps to “solve for x” (i.e. change the subject of the formula to x) for each formula. Note that in the first formula the square root of x² is |x|, so there are two cases unless you assume x is nonnegative. ────────────────────────────── 7.2.1 m = √(x²) + a·x Since √(x²) = |x|, you have two cases: • Case 1. Assume x ≥ 0 so that |x| = x:   m = x + a·x = (1 + a)x.   Assuming 1 + a ≠ 0, solve for x:    x = m/(1 + a). • Case 2. Assume x < 0 so that |x| = –x:   m = (–x) + a·x = (a – 1)x.   Assuming a – 1 ≠ 0, solve for x:    x = m/(a – 1). If additional context indicates x is nonnegative, then x = m/(1 + a) is the answer. ────────────────────────────── 7.2.2 Q = m·c·(y – x) Solve for x by isolating the (y – x) term:   Divide both sides by m·c (assuming m·c ≠ 0):    y – x = Q/(m·c)   Subtract Q/(m·c) from y:    x = y – Q/(m·c) ────────────────────────────── 7.2.3 m(m·x – n) – n(n·x – m) = m²n² Step 1. Expand the left‐hand side:   m(m·x – n) = m²x – m·n,   n(n·x – m) = n²x – n·m. So the equation becomes:   (m²x – m·n) – (n²x – n·m) = m²n² Step 2. Distribute the minus sign:   m²x – m·n – n²x + n·m = m²n² Notice that –m·n + n·m = 0, so the x–terms combine:   (m² – n²)x = m²n² Step 3. Solve for x (provided m² – n² ≠ 0):   x = (m²n²) / (m² – n²) ────────────────────────────── Summary of Answers: 7.2.1 • For x ≥ 0: x = m/(1 + a)      • For x < 0: x = m/(a – 1) 7.2.2  x = y – Q/(m·c) 7.2.3  x = m²n² / (m² – n²) These are the required forms with x as the subject of each formula.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

The Deep Dive

To solve for \( x \) in the first formula, rearrange it to find \( x \). Start by isolating \( \sqrt{x^2} \) on one side: \[ m - ax = \sqrt{x^2} \implies x = \pm (m - ax). \] Hence, \( x \) can be written as \( x = \pm (m - ax) \). For the second formula, \( Q = mc(y-x) \), first express \( y - x \): \[ y - x = \frac{Q}{mc} \implies x = y - \frac{Q}{mc}. \] Lastly, the third equation is \( m(m x - n) - n(n x - m) = m^{2} n^{2} \). Expanding and rearranging: \[ mx(m - n) = m^2 n^2 + n^2 m - n^2 \implies x = \frac{m^2 n^2 + n^2 m - n^2}{m(m - n)}. \]

preguntas relacionadas

Latest Algebra Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad